HIV incidence fall in Italy: a –20% fall in 2018 to be explained. (30th September 2020) - Salvati, S; Croci, R; Odone, A; Signorelli, C
Abstract: Background: HIV is still a critical public health threat in Europe, especially in some at-risk populations. Stigma keeps undermining access to prevention, diagnosis, and care. Treatment as Prevention (TasP) and Pre-Exposure Prophylaxis (PrEP) have spread heterogeneously across the continent. The study aimed to compare recent HIV incidence trends in five European countries (Italy, Spain, Germany, France, UK), and to speculate about TasP and PrEP's relative contribution as preventive measures in Italy. Methods: We collected incidence data by consulting the ECDC HIV/AIDS Surveillance Report 2019, and a preliminary Italian 2019 report issued by the National Institute of Health. We used the latest ECDC Continuum of HIV care data to appraise European trends in HIV viral suppression. Results: All the considered European countries reported a decreasing trend in 2018, compared to 2017. In Italy, according to raw preliminary data, the number of new HIV infections dropped from 3, 561 (5.9/100, 000) to 2, 847 (4.7/100, 000), thus resulting in a -20% fall. Interestingly, Spain shows an even sharper decrease of -22%, dropping from 3, 795 new cases in 2017 to 2, 527 in 2018, that is from a rate of 8.2/100, 000 to 6.4/100, 000. Conclusions: Since 2008, when the coordinated ECDC/WHO Regional Office for Europe HIV/AIDS surveillance system was set up, Italy has never witnessed such a sharp yearly fall in incident cases, thus representing, together with Spain, an epidemiological peculiarity in the European context. TasP could have played a major role in Italy. Indeed, Continuum of HIV care data show a positive trend in viral suppression in European countries. PrEP has been introduced in the Italian guidelines in 2016 and is nowadays adopted in a few urban areas, as a co-pay, on-demand service for high-risk populations with limited diffusion. It is thus plausible that PrEP carries a much lower epidemiologic weight in the Italian 2018 incidence reduction. Key messages: We need to spread PrEP, TasP and screening programs, especially in at-risk populations. We must search for a causal association between preventive measures and decreasing incidence.